Cybersecurity of the municipal infrastructure - S. V. Kaliakin; Yu. M. Onishchenko; V. V. Nosov (Law and Safety)
A modern city is a complex system that requires a unified systematic approach to ensuring public safety, law and order and environmental safety in the face of high levels of both man-made and natural risks. Due to the growing role of information technology in the functioning of a modern city, the threat of cyberattacks on critical municipal infrastructure has increased. The cost of such cyber-attacks can be very high, both for individual victims and for society as a whole. Cyberattacks can lead to the theft of sensitive information, data destruction or the disclosure of personal data. In addition, such attacks can lead to loss of working time and suspension of systems, which can have serious consequences for the city’s viability.